Do stroke patients screened as lower‐nutritional‐risk still receive dietitian assessment if indicated? A retrospective evaluation of two dietetic models of care for adult stroke patients. Issue 2 (22nd January 2019) - Porter, C.; Coleman, E.; Ross, L.; Palmer, M.
Abstract: Background: Dietetic models of care at Logan Hospital changed from all patients with a confirmed stroke receiving dietitian assessment ( Old pathway ) to only those patients screened as high‐nutritional‐risk ( Modified pathway ). However, it was unknown whether all low‐nutritional‐risk patients who were indicated for dietitian assessment for nutrition support actually received assessment. This pre–post retrospective study evaluated whether the Old pathway and the Modified pathway were equally effective in identifying low‐nutritional‐risk stroke patients who were indicated for dietitian assessment and compared the time spent providing Dietetic care. Methods: For both pathways, medical charts were reviewed for low‐nutritional‐risk patients admitted between December 2012 and November 2017 with a confirmed stroke, who were given a standard food and fluid diet code and scored MST < 2 (Malnutrition Screening Tool) on admission. Data collected included demographics, anthropometrics, malnutrition assessment, dietetic intervention and time spent caring for patients. Malnutrition‐related clinical indicators were used to classify patients as either Dietitian Assessment for Nutrition Support Indicated or Not Indicated . Results: Low‐nutritional‐risk patients were similar on the Old ( n  = 180) and Modified ( n  = 206) pathways [mean (SD) 66 (13) years, 63% male, 4% malnutrition]. Those classified as Dietitian Assessment for Nutrition Support Indicated ( n  = 61 of 180) were older, had a longer length of stay ( P  < 0.05), and were all identified by the Dietitian on both pathways . Ten minutes less dietetic time per patient was required on the Modified pathway ( P  < 0.001). Conclusions: The Modified Nutrition Stroke pathway performed more efficiently than the Old pathway and was equally effective at ensuring that stroke patients who were determined as being low‐nutritional‐risk received dietitian assessment during admission if indicated.